Disease Control Priorities, Third Edition : Volume 7. Injury Prevention and Environmental Health - Mock, Charles N.; Nugent, Rachel; Kobusingye, Olive; Smith, Kirk R. (Washington, DC: World Bank, 2017)
The substantial burden of death and disability that results from interpersonal violence, road traffic injuries, unintentional injuries, occupational health risks, air pollution, climate change, and inadequate water and sanitation falls disproportionally on low- and middle-income countries. Injury Prevention and Environmental Health addresses the risk factors and presents updated data on the burden, as well as economic analyses of platforms and packages for delivering cost-effective and feasible interventions in these settings. The volume's contributors demonstrate that implementation of a range of prevention strategies-presented in an essential package of interventions and policies-could achieve a convergence in death and disability rates that would avert more than 7.5 million deaths a year.